2021
DOI: 10.1093/jas/skab272
|View full text |Cite
|
Sign up to set email alerts
|

Responses to an intra-articular lipopolysaccharide challenge following dietary supplementation of Saccharomyces cerevisiae fermentation product in young horses

Abstract: Dietary intervention may be a valuable strategy to optimize the intra-articular environment in young horses to prolong their performance career. To test the hypothesis that dietary supplementation of a Saccharomyces cerevisiae fermentation product would reduce markers of joint inflammation and increase markers of cartilage metabolism following a single inflammatory insult, Quarter Horse yearlings (mean ± SD; 9 ± 1.0 mo) were balanced by age, sex, body weight (BW), and farm of origin and randomly assigned to: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Ponies fed for 8 weeks with an SCFP product displayed a more rapid decrease in cortisol levels after exercise and little or no exercise-increased serum amyloid A or cytokine levels [ 17 ]. The SCFP feeding of young horses for 84 days resulted in lower prostaglandin E2 levels in the synovium after LPS injection into the carpal joint [ 18 ]. Previously, we reported that feeding SCFP to racehorses altered the circulation behavior of blood leukocyte subpopulations after an influenza booster [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ponies fed for 8 weeks with an SCFP product displayed a more rapid decrease in cortisol levels after exercise and little or no exercise-increased serum amyloid A or cytokine levels [ 17 ]. The SCFP feeding of young horses for 84 days resulted in lower prostaglandin E2 levels in the synovium after LPS injection into the carpal joint [ 18 ]. Previously, we reported that feeding SCFP to racehorses altered the circulation behavior of blood leukocyte subpopulations after an influenza booster [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Variations in RR values were probably related to the time of day of the collection. HR, RR, and RT increases could be related to the release of inflammatory mediators due to LPS injection or pain ( 39 , 43 , 45 , 46 ). However, these parameters alone are non-specific for determining the presence and severity of pain and can be influenced by external factors ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In monogastric animals and ruminants, as well as chickens, SCFPs were able to produce a direct interaction of pre- and postbiotic ingredients with local gut epithelial [ 90 , 91 ] and immune cells [ 92 ], modulating both systemic and mucosal immune responses [ 93 ]. Preliminary information on dietary SCFPs in horses evidenced a stress-mitigating effect when young horses were subjected to prolonged exercise [ 94 , 95 ]; this is an additional main point of interest to be further elucidated, with respect to how SCPF-mediated pathways can affect and regulate inflammatory responses in horses.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%